2011
DOI: 10.1039/c1cc14292e
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective synthesis of 2-methyl indolines by palladium catalysed asymmetric C(sp3)–H activation/cyclisation

Abstract: The first example of the enantioselective methyl C-H activation by an intramolecular ArPdX species and subsequent cyclisation was developed. Palladium catalysts using commercially available chiral diphosphines yield good ee's (up to 93% ee) in the synthesis of 2-methyl indolines from 2-halo N-isopropyl anilides. This approach was also employed for the synthesis of enantioenriched cyclohexyl fused indolines with moderate enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(58 citation statements)
references
References 37 publications
0
55
0
3
Order By: Relevance
“…The groups of Kagan [9] and Cramer [10] chose the chiral phosphine ligands Duphos and Sagephos, respectively; the latter outperformed the former. Related research, aimed at substituted chiral indanes, was published by Baudoin et al [11] Experimental studies showed that a palladium-coordinated carboxylate ligand was important for the reaction and computational analysis pointed to an inner-sphere, carboxylate-assisted CMD pathway analogous to that formulated previously for C Ar ÀH functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…The groups of Kagan [9] and Cramer [10] chose the chiral phosphine ligands Duphos and Sagephos, respectively; the latter outperformed the former. Related research, aimed at substituted chiral indanes, was published by Baudoin et al [11] Experimental studies showed that a palladium-coordinated carboxylate ligand was important for the reaction and computational analysis pointed to an inner-sphere, carboxylate-assisted CMD pathway analogous to that formulated previously for C Ar ÀH functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…[183] Thus, tricyclic 459 can be obtained from vinyl triflate 457.F or the activation of primary CÀHb onds,K agan and co-workers showed that the use of chiral phosphine Me-DUPHOS (LG12)a llows for the desymmetrization of vinyl bromide 460 to access indoline 461 (Scheme 86). [184] Fort he synthesis of enantiomerically enriched dihydroindene 463 from vinyl bromide 462,C lot, Baudoin, and co-workers utilized axially chiral phosphine LG13 (Scheme 87). [185] TheY uresearch group demonstrated an enantioselective palladium-catalyzed carbonyl-directed C(sp 3 )ÀHa ctivation.…”
Section: Transfer Of Nitrenesmentioning
confidence: 99%
“…5a,c,6,7a In contrast, a single example of fused indoline-cyclobutane has been reported in its racemic form by Fagnou and co-workers. 23 Using our optimized conditions, compounds 2aa and 2ab were obtained with high enantioselectivity (e.r.…”
Section: Resultsmentioning
confidence: 99%